Clinically relevant body composition methods for obese pediatric patients - Alexandra Kreissl; Anselm Jorda; Katharina Truschner; Gabriele Skacel; Susanne Greber-Platzer (BMC, 2019)
Abstract Background There is no gold standard in body composition measurement in pediatric patients with obesity. Therefore, the aim of this study was to investigate if there are any differences between two bioelectrical impedance analysis techniques performed in children and adolescents with obesity. Methods Data were collected at the Department of Pediatrics and Adolescent Medicine in Vienna from September 2015 to May 2017. Body composition measurement was performed with TANITA scale and BIA-BIACORPUS. Results In total, 38 children and adolescents (age: 10-18 years, BMI: 25-54 kg/m2) were included. Boys had significantly increased fat free mass (TANITA p = 0.019, BIA p = 0.003), total body water (TANITA p = 0.020, BIA p = 0.005), and basal metabolic rate (TANITA p = 0.002, BIA p = 0.029). Girls had significantly increased body fat percentage with BIA (BIA p = 0.001). No significant gender differences of core abdominal area have been determined. TANITA overestimated body fat percentage (p < 0.001), fat mass (p = 0.002), and basal metabolic rate (p < 0.001) compared to BIA. TANITA underestimated fat free mass (p = 0.002) in comparison to BIA. The Bland Altman plot demonstrated a low agreement between the body composition methods. Conclusions Low agreement between TANITA scale and BIA-BIACORPUS has been observed. Body composition measurement should always be performed by the same devices to obtain comparable results. At clinical routine due to its feasibility, safety, and efficiency, bioelectrical impedance analysis is appropriate for obese pediatric patients. Trial registration ClinicalTrials NCT02545764. Registered 10 September 2015.